NONTRADITIONAL ALCOHOL AND OPIOID AGONIST TREATMENT INTERVENTIONS - Christopher, Fairgrieve (Med Clin North Am, 2018)
Despite the availability of effective medications and psychosocial interventions for the management of a substance use disorder (SUD), some individuals repeatedly fail the most aggressive treatment regimens. For such individuals, alternative treatment options exist seeking to mitigate the negative consequences of the use of harmful substances. Participation in a managed alcohol program or the use of sustained release oral morphine or injectable opioid agonist treatment, are examples of such non-standard approaches. This chapter will review the available evidence of these treatment modalities.